A unique case of protein-losing enteropathy as a complication of segmental arterial mediolysis - Nedaa Skeik, MD, FACC, FACP, FSVM, RPVI; Rebecca Windschitl, MD; Naureen Qadri, MD; Jesse Manunga, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Protein-losing enteropathy (PLE) can be caused by erosive and nonerosive gastrointestinal diseases, mesenteric lymphatic obstruction, and increased central venous pressure. Superior mesenteric artery pathology (SMAP), including dissection or occlusion is another very rarely reported etiology. Management of PLE includes treatment of the underlying cause in addition to a low-fat, high-protein, medium-chain triglyceride diet to improve nutrition. The management of SMAP and its complications, including PLE, necessitates a multidisciplinary approach involving vascular surgeons and gastroenterologists. Treatment options include conservative measures, medical management, and, in some cases, revascularization. We report a unique case of SMAP-induced PLE leading to a fatal outcome. We further conducted a literature review with the aim of summarizing the existing literature on this topic and providing intrigued readers with the most relevant and up-to-date information on this topic in hopes of improving the care of patients presenting with this unique entity. To our knowledge, our patient represents the only case in the literature where segmental arterial mediolysis is the underlying cause of superior mesenteric artery dissection and occlusion leading to PLE.